2015
DOI: 10.1128/jb.02557-14
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Is Accompanied by Global Metabolic Changes in the Opportunistic Human Pathogen Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa uses N-acyl-homoserine lactone (AHL)-dependent quorum sensing (QS) systems to control the expression of secreted effectors. These effectors can be crucial to the ecological fitness of the bacterium, playing roles in nutrient acquisition, microbial competition, and virulence. In this study, we investigated the metabolic consequences of AHL-dependent QS by monitoring the metabolic profile(s) of a lasI rhlI double mutant (unable to make QS signaling molecules) and its wild-type progenitor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 70 publications
(78 reference statements)
8
68
0
Order By: Relevance
“…Thus, the levels of important reduction-related agents (NADP + and glutathione disulfide) that protect cells from toxic reactive oxygen species were significantly higher in QS mutants than in wild type cells [38] (Figure 3), consistent with data from a previous study indicating that the key catalase gene katG is positively controlled by QS [62]. In P. aeruginosa, the concentrations of polyamines, multifunctional molecules associated with responses to oxidative stress, are elevated in the lasI/rhlI mutant (which is unable to make AHL-QS signaling molecules) because QS activates the expression of katA and superoxide dismutase, which are involved in the detoxification of reactive oxygen species [63,64].…”
Section: Influence Of Persistent Cooperativity On Primary Metabolismsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the levels of important reduction-related agents (NADP + and glutathione disulfide) that protect cells from toxic reactive oxygen species were significantly higher in QS mutants than in wild type cells [38] (Figure 3), consistent with data from a previous study indicating that the key catalase gene katG is positively controlled by QS [62]. In P. aeruginosa, the concentrations of polyamines, multifunctional molecules associated with responses to oxidative stress, are elevated in the lasI/rhlI mutant (which is unable to make AHL-QS signaling molecules) because QS activates the expression of katA and superoxide dismutase, which are involved in the detoxification of reactive oxygen species [63,64].…”
Section: Influence Of Persistent Cooperativity On Primary Metabolismsupporting
confidence: 88%
“…Recently published results from GC-and LC-MSbased analyses of intracellular metabolites in P. aeruginosa showed that a deficiency in QS perturbed the cellular concentrations of TCA cycle intermediates, amino acids, and fatty acids [63]. TCA cycle intermediates, including citrate, malate, and succinate, were more abundant in QS mutant cells compared to wild type cells, as reported previously in B. glumae [38,63].…”
Section: Influence Of Persistent Cooperativity On Primary Metabolismmentioning
confidence: 52%
“…It is not yet clear whether redox sensing by QS regulators is important in responding to the burst of reactive oxidative species generated by the host immune system or whether this type of redox switch allows regulators to balance up-regulation of QS pathways with the potentially damaging reactive oxidative species produced through heightened metabolic activity resulting from QS activation. QS in P. aeruginosa has been linked to the expression of catalase and superoxide dismutase genes for protection against H 2 O 2 (45), and other recent reports provide increased evidence for the close connection between QS and central metabolism in P. aeruginosa (46). Although it will be interesting to know precisely how oxidative sensing by LasR might serve P. aeruginosa, it is perhaps more valuable to have learned more about this protein at the chemical level, noting multiple critical cysteines that may prove to be useful targets in working toward effective treatment of this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…utilization and nutrient transport genes were the most abundant representatives (60). A more recent study in the same species demonstrated a global impact of QS on the metabolome and proposed that QS plays a key role in metabolic rewiring of the cell under certain conditions (61). A study examining the targets of LuxR homologues in Brucella, an intracellular pathogen, identified a large number of proteins involved in metabolic pathways, such as central metabolism or amino acid metabolism, respiration, and transport of amino acids and sugars that were under the control of QS regulators (62).…”
Section: Figmentioning
confidence: 99%